2017
DOI: 10.3390/rs9121263
|View full text |Cite
|
Sign up to set email alerts
|

CloudSat-Based Assessment of GPM Microwave Imager Snowfall Observation Capabilities

Abstract: Abstract:The sensitivity of Global Precipitation Measurement (GPM) Microwave Imager (GMI) high-frequency channels to snowfall at higher latitudes (around 60 • N/S) is investigated using coincident CloudSat observations. The 166 GHz channel is highlighted throughout the study due to its ice scattering sensitivity and polarization information. The analysis of three case studies evidences the important combined role of total precipitable water (TPW), supercooled cloud water, and background surface composition on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 45 publications
3
78
0
Order By: Relevance
“…The majority of the coincidences are found at around 60°N/S (Figure 2 (see also Figure 1 from Panegrossi et al [43]). Numerous ancillary products are also available, including surface information (ground elevation, land-sea flag), CPR precipitation products [e.g., 2C-SNOW-PROFILE (2CSP)] and environmental variables [total precipitable water (TPW), 2-meter temperature (T2m)].…”
Section: Gmi-cpr Databasementioning
confidence: 73%
See 4 more Smart Citations
“…The majority of the coincidences are found at around 60°N/S (Figure 2 (see also Figure 1 from Panegrossi et al [43]). Numerous ancillary products are also available, including surface information (ground elevation, land-sea flag), CPR precipitation products [e.g., 2C-SNOW-PROFILE (2CSP)] and environmental variables [total precipitable water (TPW), 2-meter temperature (T2m)].…”
Section: Gmi-cpr Databasementioning
confidence: 73%
“…Several studies (e.g., [40][41][42][43]48]) indicated that the presence of supercooled droplets on the top of the snow clouds could strongly affect TBs from high frequency channels. Specifically, supercooled droplets tend to partially mask scattering by snow crystals, which complicates the detection of snow using passive microwave radiometers.…”
Section: Complementary Datasetmentioning
confidence: 99%
See 3 more Smart Citations